HIF-1α and HIF-2α: siblings in promoting angiogenesis of residual hepatocellular carcinoma after high-intensity focused ultrasound ablation. - Lun Wu; Zhihao Fu; Shiji Zhou; Jianping Gong; Chang An Liu; Zhengrong Qiao; Shengwei Li (PLoS ONE)
Background High-intensity focused ultrasound (HIFU) is a widely applied to treatment for unresectable hepatocellular carcinoma. However, insufficient HIFU can result in rapid progression of the residual tumor. The mechanism of such rapid growth of the residual tumor after HIFU ablation is poorly understood. Objective The aim of this study was to investigate the dynamic angiogenesis of residual tumor, and the temporal effect and mechanism of the HIF-1, 2α in the residual tumor angiogenesis. Methods Xenograft tumors of HepG2 cells were created by subcutaneously inoculating nude mice (athymic BALB/c nu/nu mice) with hepatoma cells. About thirty days after inoculation, all mice (except control group) were treated by HIFU and assigned randomly to 7 groups according to various time intervals (1st, 3rd, 5th day (d) and 1st, 2nd, 3rd, 4th week (w)). The residual tumor tissues were obtained from the experimental groups at various time points. Protein levels of HIF-1α, HIF-2α, VEGF-A, and EphA2 were quantified by immunohistochemistry analysis and Western Blot assays, and mRNA levels measured by Q-PCR. Microvascular density was calculated with counting of CD31 positive vascular endothelial cells by immunohistochemical staining. Results Compared with the control group, protein and mRNA levels of HIF-1α reached their highest levels on the 3rd day (P<0.01), then decreased (P<0.05). HIF-2α expression reached its highest level on the 2nd week compared with control group (P<0.01), then decreased (2 w-4 w) (P<0.05). The protein and mRNA levels of VEGF-A and EphA2 in the residual tumor tissues group that received HIFU were significantly decreased until 1 week compared with the control group (P<0.01). However, the levels increased compared to controls in 2-4 weeks (P<0.05). Similar results were obtained for MVD expression (P<0.05). Conclusion Insufficient HIFU ablation promotes the angiogenesis in residual carcinoma tissue over time. The data indicate that the HIF-1, 2α/VEGFA/EphA2 pathway is involved.